Sport tourism: Physically-disabled sport tourists’ orientation - Khor, Poy Hua; Ibrahim, Irini; Lim, Khong Chiu (Elsevier Ltd., 2013)
It is a challenge for sport tourism providers to organize the exceptional demand of physically-disabled individuals.Analyzing the orientation of physically-disabled in sport tourism participation provides the basis for further theoretical recognition of constraints and negotiations in sport tourism in general, besides facilitating related providers and policy makers in understanding of strategies development to promote sporting events among individuals with disability. The objective of the current paper is answered based on survey research conducted in a representative sample of 312 physically-disabled Malaysian. According to the results, physically-disabled Malaysian struggle with a mix of structural constraints, interpersonal constraints, intrapersonal constraints, and cultural constraints. Majority of them are structurally constrained in sporting event participation. Although transportation is the main constraint factor, participations are possible through adoption of interpersonal coordination strategies, skill acquisition strategies, time management strategies, and financial resources strategies